From paper to plastic: Understanding the impact of eWIC on WIC recipient behavior. (February 2019) - Hanks, Andrew S.; Gunther, Carolyn; Lillard, Dean; Scharff, Robert L.
Highlights: eWIC reduces time and potential stigma for WIC recipients. Transition to eWIC increased household WIC benefit redemptions. Introduction of eWIC had no impact on purchases of other goods. There is potential for states to partner with grocers to improved WIC redemptions. Abstract: Evidence shows that the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) is underutilized. WIC enrolls 52.7% of eligible persons and participants claim a fraction of available benefits. Researchers suggest that people underutilize WIC because of the time needed to enroll in and use WIC and because participants may believe that, if others notice them participating in WIC, community members will stigmatize them. Recently enacted policies may reduce both time costs and potential for stigma associated with WIC. Congress mandated that, by 2020, all states disburse WIC benefits through an Electronic Benefits Transfer (eWIC) system. Given that eWIC reduces the time required for each transaction and and makes it more difficult to identify beneficiaries, we expect WIC redemptions to increase. In addition, eWIC might also increase the chance WIC recipients choose non-WIC foods for redemption increasing non-WIC expenditures. To measure the impact of eWIC on WIC redemptions and non-WIC food expenditures we analyze data on grocery expenditures of 11, 887 WIC-participating households in one state over the period it implemented eWIC. We find that, after beneficiaries began redeeming WIC benefits through eWIC, spending on non-WIC eligible foods did not change but redemptions of WIC benefits increased.